Perwujudan Nilai-Nilai Pancasila Dalam Kehidupan Berbangsa Dan Bernegara - Lutviana Datau (EduPsyCouns: Journal of Education, Psychology and Counseling, 2022)
Abstract: This study aims to determine the implementation of Pancasila values for the material principles of drafting legislation contained in Article 6 of the Constitution No. 12/2011 this study aims to provide knowledge to the public about the importance of understanding Pancasila, this research is a type of qualitative research using the roles, functions, and history contained in the values of Pancasila. Based on the results of the research and discussion, conclusions were also drawn and in the principle of material content an explanation of the values of Pancasila was made. Abstrak: Penelitian ini bertujuan mengetahui implementasi nilai-nilai pancasila untuk asas materi muatan penyusunan perundang-undangan terdapat dalam pasal 6 UUD No. 12/2011 penelitian ini bertujuan untuk memberi pengetahuan masyarakat betapa pentingnya pemahaman pancasila, penelitian ini merupakan jenis penelitian kualitatif dengan menggunakan peran, fungsi, dan sejarah yang terdapat dalam nilai-nilai pancasila. Berdasarkan dalam hasil penelitian dan membahas juga dihasilkan kesimpulan dan dalam asas materi muatan telah membuat penjelasan nila-nilai pancasila.